2015
DOI: 10.21608/eja.2019.46730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fructooligosaccharide supplementation on feed utilization and growth performance of Nile tilapia (Oreochromis niloticus) fingerlings

Abstract: Effect of dietary fructooligosaccharide supplementation on feed utilization and growth performance of Nile tilapia (Oreochromis niloticus) fingerlings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…This is consistent with the results reported by Ab El‐latif et al. (2015), who mentioned that digestive enzyme activity correlated with microvilli after prebiotic administration.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results reported by Ab El‐latif et al. (2015), who mentioned that digestive enzyme activity correlated with microvilli after prebiotic administration.…”
Section: Discussionsupporting
confidence: 93%
“…FOS, short and medium chains of β-D-fructans, can be fermented by certain bacteria such as lactobacilli and bifidobacterial so after dietary supplemented, it would improve the growth and survival of such bacteria in the GI tract of animals ( 13 ). FOS supplemented feed could enhance intestinal enzymes activities, absorptive ability, and histological features of intestinal villi and subsequently improve the feed utilization and growth performance of Nile tilapia ( 14 ). Tilapia fed a diet supplemented with 20–30 g FOS/ kg (3%) enhanced immune responses, reduced oxidative stress, and increased survival rates when infected with A. hydrophila ( 15 ) while Abd El-Gawad et al ( 16 ) reported that 2% dietary FOS was the most suitable and beneficial dose for Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the dietary supplementation of FOS significantly promoted WG and FCR, which indicated that FOS produced positive effects on growth performance. Similarly, dietary FOS was also reported to improve growth parameters in stellate sturgeon (Akrami et al., 2013), blunt snout bream (Zhang, Li, et al, 2014), Nile tilapia (Abd El‐latif, Abd El‐Gawad, & Emam, 2015) and Chinese mitten crab (Jia et al., 2017). In addition, the retention of protein and lipid, and the apparent digestibility coefficient of DM and CP were significantly advanced by FOS supplementation in this study.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the dietary FOS significantly promoted intestinal villus height and amylase activity. Similarly, the dietary FOS supplemented groups improved intestinal structures of blunt snout bream (Zhang, Li, et al, 2014) and Nile tilapia (Abd El‐latif et al., 2015). In addition, the dietary FOS also advanced the amylase activity in intestine of Caspian roach (Soleimani et al., 2012), blunt snout bream (Wu et al., 2013) and turbot ( Scophthalmus maximus L.) (Guerreiro, Enes, Rodiles, Merrifield, & Oliva‐Teles, 2015).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation